Synthesis, characterization, electrochemistry and spectroelectrochemistry of novel soluble porphyrazines bearing unsaturated functional groups - Tuncer, Serap; Koca, Atif; Gul, Ahmet; Avciata, Ulvi (ELSEVIER SCI LTD, 2012)
Metalloporphyrazines with a 2-methyl-2-pentenyl group fused to each pyrrole unit were synthesized starting with the corresponding unsaturated dicarbonitrile derivative. The new compounds were characterized by elemental analysis together with FTIR, (1)H-NMR, and UV-Vis spectroscopy and via voltammetric and spectrochemical methods. Electrochemical and spectroelectrochemical measurements demonstrate that while metal-free and magnesium porphyrazines gave common porphyrazine (Pz) ring-based electron-transfer reactions, incorporating redox active metal center, Co(II), into the porphyrazine core extended the redox activity of the ring system with reversible metal-based reduction and oxidation couples of the metal center in addition to the common Pz ring-based electron transfer processes. The unsaturated functional groups of the porphyrazines did not alter the common electrochemical behavior of the complexes. An in situ electrocolorimetric method, based on the 1931 CIE (Commission Internationale de l'Eclairage) system of colorimetry, was applied to investigate the color of the electro-generated anionic and cationic forms of the complexes for possible electrochromatic applications. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Porphyrazines; Magnesium; Cobalt; Spectroelectrochemistry; Cyclic Voltammetty; Chromaticity diagram; APPENDED PYRIDINE RINGS; METAL-COMPLEXES; BEHAVIOR; PHTHALOCYANINES; SUBSTITUENTS; TETRA-2,3-PYRAZINOPORPHYRAZINES; TETRAAZAPORPHYRIN; SPECTROSCOPY; PORPHYRINS; Chemistry; Engineering; Materials Science